Customized IoT Enabled Wireless Sensing and Monitoring Platform for Smart Buildings. (2016) - Shah, Jalpa; Mishra, Biswajit
Abstract: In this paper we present a customized Internet of Things (IoT) enabled Wireless Sensing and Monitoring Platform to monitor the temperature, relative humidity and light in the context of building automation. In developed system, data is sent from the transmitter node to the receiver node through a customized hopping method. The data received at the receiver node is monitored and recorded in an excel sheet in a personal computer (PC) through a Graphical User Interface (GUI), made in LabVIEW. An Android application has also been developed through which data is transferred from LabVIEW to a smartphone through which data is remotely monitored.